EVALUASI SISTEM AKUNTANSI PEMBELIAN BAHAN BAKU PADA PT. LKD MULTI INDUSTRI - Ita Mustika; Khadijah Khadijah; Elvi Noviawati (Program Studi Akuntansi, 2022)
Inventory of raw materials is the main element that needs to be considered in carrying out production activities. The limited amount of raw material inventory will hamper the smooth production process and will reduce customer confidence in the company. Inventory of raw materials has an important role in the production process. The use of raw materials must be in accordance with sales orders received from customers. The data analysis method used in this research is qualitative analysis with a descriptive approach. The term